Required and desired: breakthroughs for future-proofing mineral and metal extraction - Elisabeth Clausen; Aarti Sörensen (Mineral Economics, 2022)
The global industrial mining sector is, like other sectors, undergoing an unprecedented transformation pushed by global sustainability and climate challenges. The need to increase productivity and efficiency of mineral extraction along with increasing pressure from a wide range of stakeholders to decarbonise the industry and make mining practices more sustainable, accountable, and socially acceptable are driving the adoption of automation and digitalisation technologies as well as the electrification of equipment and the implementation of more sustainable energy solutions for the industry. Automation and digitalisation are changing the way minerals and metals are extracted and provide important tools for designing and implementing the mine of the future: a digitally integrated, autonomous mine where no humans need to be put in harm's way and in which the connected systems are able to reduce the ever-increasing complexity to such an extent that improved decision-making can be realised in real time. Mining as an industry still has a way to go to reach the potential of automation and digitalisation on the one hand, and alternative drive systems and sustainable power generation on the other. This paper will give an overview of empirically derived leading technologies underlying the current transformation and will place them in the context of the data-information-value-chain that can provide a more systematic approach to describe the various technologies and, in particular, their interrelationships. This can support a better understanding of assessing the overall technological maturity of an operation, especially with respect to their evolution from automation of equipment towards autonomous systems. There is no reason to doubt that, from a technology perspective, the digitally connected, autonomous, and carbon-free mine have the potential to become a reality. Breakthrough effects can be expected to come not from any single technology but rather from successfully developing, implementing, and integrating the full suite of (available) automation and digitalisation technologies across entire mining operations and moving towards digitally integrated, autonomous systems considering the process and its interrelations holistically (Clausen et al.~ 13 ). However, in order to get there, mining companies need to consider not only the technological aspects of this transformation. For successfully responding to the changing landscape of stakeholder expectations and future-proofing the industry requires, the authors argue that mining companies need to adopt a mind-set of the human-centred climate smart mine (Clausen and Sörensen 12 ). In addition, mining companies need to reconsider their role in the economic, social, and environmental ecosystem they are embedded in so they can break through traditions that keep them from successfully positioning themselves as builders of social value.
Keywords: 660; Mining; Digitalisation; Metals